Development of a New Tool for 3D Modeling for Regenerative Medicine. (13th June 2011) - Mattoli, Filippo; Tiribuzi, Roberto; D'Angelo, Francesco; di Girolamo, Ilaria; Quattrocelli, Mattia; Montesano, Simona; Crispoltoni, Lucia; Oikonomou, Vasileios; Cusella De Angelis, Maria Gabriella; Marconi, Peggy; Orlacchio, Antonio; Sampaolesi, Maurilio; et al.
Abstract : The effectiveness of therapeutic treatment based on regenerative medicine for degenerative diseases (i.e., neurodegenerative or cardiac diseases) requires tools allowing the visualization and analysis of the three-dimensional (3D) distribution of target drugs within the tissue. Here, we present a new computational procedure able to overcome the limitations of visual analysis emerging by the examination of a molecular signal within images of serial tissue/organ sections by using the conventional techniques. Together with the 3D anatomical reconstitution of the tissue/organ, our framework allows the detection of signals of different origins (e.g., marked generic molecules, colorimetric, or fluorimetric substrates for enzymes; microRNA; recombinant protein). Remarkably, the application does not require the employment of specific tracking reagents for the imaging analysis. We report two different representative applications: the first shows the reconstruction of a 3D model of mouse brain with the analysis of the distribution of the β -Galactosidase, the second shows the reconstruction of a 3D mouse heart with the measurement of the cardiac volume.